HUBUNGAN FREKUENSI KEBERANGKATAN KAPAL 3 GT DENGAN JUMLAH LOGISTIK MELAUTNYA DI PPI DUMAI PADA MUSIM BARAT DAN MUSIM TIMUR - Zain, Jonny; Syaifuddin, Syaifuddin; Rohmatin, Khoiru (Fakultas Perikanan dan Kelautan Universitas Riau, 2009)
This research was carried out on March to April 2010 at Dumai FishingPort, with the purposes to know the relationship between departure of fishingvessel 3 GT frequencies with logistic amount on West and East season. Thisresearch activity used survey method. There are high correlation between Westand East fishing operation season. Departure fishing vessel frequency was higheron West season than East season. This was illustrated at linear regression y =142,0x + 51,37 (fuel), y = 318,5x + 11,48 (ice), y = 135,6x + 139,0 (fresh water)on West season and y = 159,3x + 23,53 (fuel), y = 403,8x + 45,82 (ice), y =140,9x + 92,21 (fresh water) on East season.